MULTIMEDIA-ENHANCED ENGLISH LANGUAGE TEACHING: CURRENT PRACTICES AND FUTURE PEDAGOGICAL TRENDS - N. SIVAKAMI,; Dr.S.GUNASEKARAN, (The Bioscan, 2026)
The growing use of digital technologies has brought a major shift in the way English is taught and learned across educational contexts. Multimedia tools such as videos, audio materials, interactive applications, online platforms, and digital storytelling have created more engaging and learner- centered classrooms in English Language Teaching (ELT). This paper examines how multimedia is currently used in ELT classrooms and explores future pedagogical trends that are likely to shape language education in the coming years. It discusses how multimedia supports the development of the four language skills—listening, speaking, reading, and writing—by providing authentic language exposure, visual support, and opportunities for active participation. The paper also highlights emerging innovations such as artificial intelligence–based learning tools, virtual and augmented reality environments, adaptive learning systems, and personalized digital instruction. These technologies offer new possibilities for immersive learning, instant feedback, and flexible learning pathways suited to diverse learner needs. While multimedia brings many advantages, including improved motivation, autonomy, and communication skills, the paper also addresses practical challenges such as limited access to technology, teacher training requirements, and the need for thoughtful pedagogical planning. Overall, the study emphasizes that multimedia can greatly enhance English language learning when integrated purposefully into curriculum design and classroom practice. By aligning technological tools with sound teaching principles, educators can create meaningful learning experiences that prepare students for effective communication in a digitally connected world.